Single-cell sequencing of brain tissues reveal the central nervous system’s susceptibility to SARS-CoV-2 and the drug - Lu, Zhichao; Wang, Ziheng; Song, Zhuhuan; Chen, Chen; Ma, He; Gong, Peipei; Xu, Yunzhao (Frontiers in Pharmacology, 2022)
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) led to the current worldwide COVID-19 epidemic, resulting in a public health crisis that required immediate action. The SARS-CoV-2 virus enters human cells via three receptors, namely the cathepsin, the angiotensin-converting enzyme 2 (ACE2), and the SARS-CoV receptors. Cathepsin destroys the spike protein (S protein), resulting in the entry of viral nucleic acid into the cells of human hosts. Methods: Utilizing single-cell transcriptome analysis of brain tissue, the present research investigated the vulnerability of the central nervous system (CNS) to infection with SARS-CoV-2 in humans. Results: ACE2 is mainly expressed in endothelial cells. Meanwhile, the aging endothelial cells expressed more ACE2. Drug prediction suggests that (-)-catechin may reduce the effects of COVID-19 on the nervous system. The results of immunohistochemistry showed that ACE2 was mainly expressed in cerebral vessels. IF results showed that the co-expression of CD31 and ACE2. The WB showed that ACE2 expressed higher in old rats than young rats. Conclusions: These results provide insight into the process of SARS-CoV-2 brain invasion and indicate that patients with neurological symptoms who are infected with SARS-CoV-2 should be given individualized care.